IbIKK BUDIDAYA IKAN PATIN (Pangasius sp) DI KOLAM TERPAL - Eva Ayuzar; Zuriani - (DHARMA RAFLESIA, 2018)
The aim of IbIKK programme on cultivating pangasius fish in tarpaulin pond specifically for nursing the fish is to develop the pangasius aquaculture in Aceh Province. Therefore, by this programme, society and students could know the method of pangasius cultivating. Moreover, the society could recognize pangasius fish for both its taste and its advantages. This nursing activity is conducted for six months. During production time in activity of nursing pangasius fish in tarpaulin pond, the growth of fish reached 350-400 grams and its survival rate was up to 80%. Furthermore, this IbIKK programme was also carried out for student’s activities such as field work practice, research, and practical in learning activity.Keywords: pangasius fish, tarpaulin pond, cultivating